Migration and Intercultural Relations, Human Rights and democratic Citizenship - Mesić, Milan, sociolog (2010)
The presentation represents the concepts of the Croatian courses within the Joint European MA "Migration and Intercultural Relations", dealing with international migration, intercultural education, multiculturalism, transnationalism, human rights and ethnic conflicts.
Projekt MZOS
ENG